2023
DOI: 10.3389/fonc.2022.1038932
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lipid droplet metabolism patterns identified prognosis and tumor microenvironment infiltration in gastric cancer

Abstract: BackgroundGastric cancer is one of the common malignant tumors of the digestive system worldwide, posing a serious threat to human health. A growing number of studies have demonstrated the important role that lipid droplets play in promoting cancer progression. However, few studies have systematically evaluated the role of lipid droplet metabolism-related genes (LDMRGs) in patients with gastric cancer.MethodsWe identified two distinct molecular subtypes in the TCGA-STAD cohort based on LDMRGs expression. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…ABCA1 is involved in the progression of various cancers and pathological biological processes, including dyslipidemia, neurological disorders, glaucoma, and diabetes [ 8 ] However, the effect of ABCA1 on the heterogeneous TME of GAC has not been fully elucidated. Nevertheless, Liu et al employed bioinformatics techniques to develop a lipid droplet metabolism model for GAC and revealed that upregulated ABCA1 might contribute to the development of unfavorable clinical characteristics in GAC [ 27 ]. Similarly, Yin et al discovered a correlation between ABCA1 expression and drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…ABCA1 is involved in the progression of various cancers and pathological biological processes, including dyslipidemia, neurological disorders, glaucoma, and diabetes [ 8 ] However, the effect of ABCA1 on the heterogeneous TME of GAC has not been fully elucidated. Nevertheless, Liu et al employed bioinformatics techniques to develop a lipid droplet metabolism model for GAC and revealed that upregulated ABCA1 might contribute to the development of unfavorable clinical characteristics in GAC [ 27 ]. Similarly, Yin et al discovered a correlation between ABCA1 expression and drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the activity of CPT1α can decrease FA β- Oxidize, thereby reducing energy supply to tumor cells and exerting anti-tumor effects ( 17 , 18 ). Furthermore, lipid droplets are formed in the endoplasmic reticulum when cellular lipids are excessive ( 19 ), which provide sufficient energy for cancer metastasis ( 20 ).…”
Section: Introductionmentioning
confidence: 99%